Determinants of Low Toddler Attendance at the Posyandu in Bobo Village, Tidore Islands City - Hestyn Amalia (Lembaga Penellitian, Pengabdian dan Publikasi (LP3M), UNIVERSITAS MUHAMMADIYAH MALUKU UTARA, 2025)
This research employed a descriptive cross-sectional study design with an alpha of 0.05. The total population consisted of 33 respondents who were mothers of infants/toddlers. This study aimed to identify the internal and external factors influencing the low attendance of mothers with toddlers at the Posyandu in Bobo Village. The results indicated that an internal factor was mothers' fear of their children developing a fever after immunization, as reported by 20 respondents (60.6%), and an external factor was the absence of Supplementary Feeding (PMT), as reported by 26 respondents (78.8%). Therefore, it can be concluded that the decline in visits by mothers with toddlers to the Posyandu is influenced by both external and internal factors. Consequently, it is necessary for health workers, Posyandu cadres, and village officials to collaborate in order to enhance public knowledge and create other innovations that will attract the community to visit the Posyandu. Monitoring the Posyandu attendance rate is crucial because the active participation of mothers with toddlers in visiting the Posyandu will influence the stunting rate in Indonesia. It is expected that a high attendance rate or active participation at the Posyandu will contribute to a lower stunting rate in Indonesia, thereby achieving the goal of Zero Stunting in Indonesia.